Geology of National Parks of Central/Southern Kenya and Northern Tanzania Geotourism of the Gregory Rift Valley, Active Volcanism and Regional Plateaus - Scoon, Roger N. (Springer International Publishing, 2018)
This book describes the interrelationship between the spectacular geology of an area of East Africa that includes a branch of the rift valley, as well as giant freestanding ice-capped mountains and extraordinarily toxic, alkaline lakes, and some of the greatest concentrations of wildlife on Earth. It suggests that geological processes that have shaped the iconic landforms, including active volcanoes, may also be responsible for the unusually diverse speciation which characterises the region. Moreover, it is not a coincidence that important palaeoanthropological discoveries have been unearthed in the region. National parks and conservation areas have tremendous potential for geotourism and the book assists both tour guides and visitors in this regard. In addition, the book may provide a better understanding to management of the importance of geology for sustaining wildlife.